Dinamika Bisnis Kuliner UMKM di Era Persaingan Lokal: Studi Kasus pada Mie Ayam Matuari di Sunbae Manado - Andalangi Maatuil, Rexy; Chelsia Tamasengge; Wisler Hito; Betlive Saban; Gusti Kareth (Indonesia Economic Journal, 2025)
This study aims to understand the competitive dynamics of culinary MSMEs in Sunbae Manado through a case study of Mie Ayam Matuari. Using a qualitative approach with case study design, the research explores marketing strategies, product innovation, business management, and the internal and external factors influencing business growth. The findings indicate that the success of Mie Ayam Matuari is driven by premium homemade product innovation, strong differentiation strategies, and effective digital marketing through social media. These results align with Schumpeter’s and Drucker’s entrepreneurship theory, Porter’s competitive advantage framework, and consumer behavior theory. The main challenges include limited labor capacity, shifting culinary trends, and increasing competition. However, customer loyalty and long-term development orientation provide significant opportunities for business sustainability. This study offers implications for strengthening culinary MSMEs through innovation, service quality enhancement, and supportive regional policies.